Mapping of the radiation field of a mammography equipment using molybdenum and rhodium filters - Jacqueline Sales Barreira; Vitor Vivolo; Daniela Campos (Brazilian Journal of Radiation Sciences)
The use of X rays for diagnostic radiology is very common and important to Medicine, including mammographic diagnosis focusing decreasing of the doses applied to the patients and preserving high quality of the diagnostic image. A quality control program of the irradiation systems it is very necessary. The Instruments Calibration Laboratory (LCI) of IPEN perform calibration in dosemeters used in radiation dosimetry (in diagnostic radiology) for many years. The objective of that paper is determining the point of greatest intensity of the beam issued by the mammograph equipment. Exposures were made with filters Rhodium and Molybdenum. That mapping is important before applied a routine quality control program of the mammograph equipment and the calibration of instruments in the diagnosis.